Emerging role of mRNA epitranscriptomic regulation in chemoresistant cancer cells - Shen, Shensi (Mol Cell Oncol, 2020)
Cancer persister cells remain a significant barrier to effective anti-cancer therapy. We found that melanoma persister cells undergo a reversible reprogramming of mRNA translation. A subset of mRNAs, harboring N6-methyladenosine in their 5ʹ-untranslated regions, is translationally up-regulated in an eIF4A-dependent manner. Targeting eIF4A prevents the emergence of resistant clones.